Disposition and metabolism of [14C] Sacubitril/Valsartan (formerly LCZ696) an angiotensin receptor neprilysin inhibitor, in healthy subjects - Flarakos, Jimmy; Du, Yancy; Bedman, Timothy; Al-Share, Qusai; Jordaan, Pierre; Chandra, Priya; Albrecht, Diego; Wang, Lai; Gu, Helen; Einolf, Heidi J.; Huskey, Su-Er; Mangold, James B. (Xenobiotica, 2016)
1. Sacubitril/valsartan (LCZ696) is an angiotensin receptor neprilysin inhibitor (ARNI) providing simultaneous inhibition of neprilysin (neutral endopeptidase 24.11; NEP) and blockade of the angiotensin II type-1 (AT1) receptor. 2. Following oral administration, [ 14 C]LCZ696 delivers systemic exposure to valsartan and AHU377 (sacubitril), which is rapidly metabolized to LBQ657 (M1), the biologically active neprilysin inhibitor. Peak sacubitril plasma concentrations were reached within 0.5-1 h. The mean terminal half-lives of sacubitril, LBQ657 and valsartan were ∼1.3, ∼12 and ∼21 h, respectively. 3. Renal excretion was the dominant route of elimination of radioactivity in human. Urine accounted for 51.7-67.8% and feces for 36.9 to 48.3 % of the total radioactivity. The majority of the drug was excreted as the active metabolite LBQ657 in urine and feces, total accounting for ∼85.5% of the total dose. 4. Based upon in vitro studies, the potential for LCZ696 to inhibit or induce cytochrome P450 (CYP) enzymes and cause CYP-mediated drug interactions clinically was found to be low.